Community social vulnerability to climate change-related hazards in selected municipalities in Laguna, Philippines - Mendoza, M. E. T. (2003)
The study examined the vulnerability of selected communities in the province of Laguna in the Philippines based as a basis for knowledge-based decisions in planned adaptations. Specifically, it endeavored to describe the communities relative vulnerability to typhoons and flooding as climate change - related to hazards, analyze the main indicators contributory to their vulnerability and generate recommendations for vulnerability research and adaptation policies. The study examined 194 barangays in terms of their exposure to flooding and typhoons as climate hazards, their sensitivity to, and specific indicators, the communities were found to have generally low exposure, high sensitivity and low capacities to adapt in the light of these hazards. Based on specific indicators, the communities were found to have generally low exposure, high sensitivity and low capacities to adapt to the impacts of climate-related hazards. The study recommends for more researches on climate change-related vulnerabilities with emphasis on social and human indicators of sensitivity and adaptive capacities. Adaptation policies must seriously consider localized social vulnerabilities of our communities.
Keywords: Climate change; Natural hazards; Laguna